Effect of Tolterodine on the Anticoagulant Actions and Pharmacokinetics of Single-dose Warfarin in Healthy Volunteers - Rahimy, Mohamad; Hallén, Bengt; Narang, Prem (Arzneimittelforschung, 2002)
This randomized, double-blind, crossover study investigated the potential effects of tolterodine ((R)-N,N-diisopropyl-3-(2-hydroxy-5-methyl-phenyl) -3-phenylpropanamine, CAS 124937-51-5), an antimuscarinic agent for the treatment of the overactive bladder, on the anticoagulant actions and pharmacokinetics of single-dose warfarin (CAS 81-81-2) in 20 healthy male volunteers. In terms of study design, volunteers randomly received oral tolterodine L-tartrate (2 mg twice daily) or matching placebo for 7 days, with a single oral dose of warfarin (25 mg) administered on day 4 of each treatment period. R-(+)- and S-(-)-warfarin pharmacokinetics were estimated from plasma levels measured up to 96 h post-dose, in conjunction with assessment of prothrombin time and factor VII activity. Pharmacokinetics of tolterodine and its active 5-hydroxymethyl metabolite ((R)-N,N-diisopropyl-3-(2-hydroxy-5-hydroxymethyl-phenyl)-3-phenylpropanamine; 5-HM), in the presence and absence of warfarin, were also determined. Relative to placebo, tolterodine had no discernible effect on the anticoagulant actions of warfarin. Point estimates of the tolterodine:placebo ratios for prothrombin time and factor VII activity were 1.00 (90 % confidence interval [CI]: 0.91-1.10) and 0.91 (90 % CI: 0.83-0.99), respectively, consistent with equivalence. No clinically significant changes in the pharmacokinetics of R-(+)- and S-(-)-warfarin were noted. Serum concentration-time profiles and the pharmacokinetics of tolterodine and 5-HM were similar in the presence and absence of warfarin. There were no safety concerns. These findings indicate that co-administration of tolterodine and warfarin is safe and well tolerated, with no clinically significant pharmacodynamic or kinetic interaction in healthy volunteers.
Keywords: CAS 81-81-2; CAS 124937-51-5; Tolterodine, clinical studies, drug interactions; Warfarin, clinical studies, drug interactions